A Bijection between Lattice-Valued Filters and Lattice-Valued Congruences in Residuated Lattices. (18th July 2013) - Wei, Wei; Qiang, Yan; Zhang, Jing
Abstract : The aim of this paper is to study relations between lattice-valued filters and lattice-valued congruences in residuated lattices. We introduce a new definition of congruences which just depends on the meet ∧ and the residuum → . Then it is shown that each of these congruences is automatically a universal-algebra-congruence. Also, lattice-valued filters and lattice-valued congruences are studied, and it is shown that there is a one-to-one correspondence between the set of all (lattice-valued) filters and the set of all (lattice-valued) congruences.